Relato de Estágio Supervisionado em Pedagogia aplicado em duas escolas municipais de Juruá - AM - Santos, Railane Ferreira Cajado dos (Brasil, 2024)
This paper presents the experience report of three supervised internships in Pedagogy carried out in the city of Juruá – AM, covering two municipal schools: the Escola Municipal Dalila Litaiff and the Escola Pró-Infância Ataíde Nobres Dias Ferreira. Each internship consisted of 150 hours, divided into 120 practical hours and 30 theoretical hours, providing an integration between theory and practice in teacher training. The first internship focused on Education Management at the Escola Municipal Dalila Litaiff, with the objective of analyzing the physical and documentary structure of the school and understanding the role of the educational manager. During this period, it was observed how efficient management directly influences the functioning and quality of teaching. The analysis included the evaluation of administrative documents, the school infrastructure and the interaction between management and the school community. This internship highlighted the importance of participatory and transparent management to create a more inclusive and welcoming school environment. The second internship was carried out at the Escola Pró-Infância Ataíde Nobres Dias Ferreira, focusing on observation and participation in the pedagogical routine with three-year-old children. This internship allowed an immersion in pedagogical practices aimed at early childhood, emphasizing the importance of the integral development of children. It was observed how the daily routine, playful activities and interactions between children and educators contribute to the cognitive, social and emotional development of children. The experience highlighted the need for careful pedagogical planning adapted to the specific needs of each age group, promoting a safe and stimulating learning environment. The third internship, again at the Escola Municipal Dalila Litaiff, involved the analysis of pedagogical practices and the dynamics of the school environment from 1st “A” to 5th “A” grade. During this internship, several teaching strategies and methodologies applied by teachers in the classroom were observed. The analysis focused on how pedagogical practices are adapted to meet students’ needs, promoting inclusion and the development of essential skills. In addition, it was possible to identify the difficulties faced by educators and propose improvements to teaching practices. This internship highlighted the importance of ongoing training and pedagogical support for teachers, aiming at the constant improvement of teaching quality. This work reflects on the lessons learned in each internship, highlighting the pedagogical and management practices that promote an inclusive and effective school environment. The experience accumulated throughout the three internships reinforces the importance of integrating theory and practice in the training of future educators. Practical experience provides a deeper understanding of school realities and students’ needs, allowingfuture pedagogues to develop critical skills to act effectively in the school environment. The supervised internships in Pedagogy carried out in the municipal schools of Juruá – AM were fundamental for teacher training. Practical experience, combined with theoretical reflection, contributed significantly to the development of essential skills for professional practice, preparing future educators to face the challenges of education and promote quality education for all.